Clinical features and current management experience in Gorham-Stout disease: a systematic review - Zilong Zhou; Tong Qiu; Jiangyuan Zhou; Zixin Zhang; Xue Gong; Xuepeng Zhang; Yuru Lan; Congxia Yang; Yujia Zhang; Shanshan Xiang; Yi Ji (Orphanet Journal of Rare Diseases)
Abstract Background Gorham-Stout disease (GSD) is a rare complex lymphatic malformation. Since its initial description in 1838, only approximately 400 patients have been documented. There is currently no consensus on the diagnostic criteria or treatment options for GSD. The objective of this study was to review the clinical characteristics of patients with GSD and determine the current diagnostic and treatment models. Methods A comprehensive search of the PubMed, Web of Science, Embase, and Cochrane Library databases was conducted to identify all relevant literature on GSD published over the decade from 2013 to 2023. The clinical information extracted from these publications was analyzed. Results A total of 206 patients with GSD were included in the study, comprising 119 males, 81 females and 6 patients with unknown sex. The age of onset of patients was widely distributed, ranging from 0 to 77 years old. However, the majority of cases occurred in childhood (50.7%). Fifteen patients (10.3%) exhibited an onset age of less than 1 year. The average time from the onset of symptoms to diagnosis was 3.5 years. The number of patients with osteolysis in the axial bone was greater than that in the appendiceal bone (P < 0.05), and the number of patients with multiple osteolytic lesions was greater than that with single osteolytic lesions (77.2% vs. 22.8%). In general, GSD was more likely to occur in the spine (46.1%), ribs (28.6%), hip (23.3%), femur (18.4%), mandible (15.5%) and humerus (15.0%). Pain was the most common symptom, with 68.4% of patients reporting pain in the lesion area. Surgery (66.9%) and bisphosphonates (56.9%) are still the mainstream treatment methods, with a total of 33 (18.2%) patients receiving sirolimus. Pleural effusion was identified as a risk factor for patient mortality (P < 0.05). Conclusions GSD is most commonly observed in children, with a slight male predisposition. It commonly manifests as multiple osteolysis of the axial bone, with pain being the most common symptom. The presence of pleural effusion indicates a serious condition that requires close monitoring to prevent mortality. Despite the advent of novel therapeutic modalities, the management of GSD remains an area in need of further investigation.